PENGEMBANGAN MULTIMEDIA INTERAKTIF MENGUNAKAN ADOBE CAPTIVATE 7.0 PADA MATA KULIAH DASAR-DASAR KOMPUTER - Nofri Hendri (Pedagogi: Jurnal Ilmu Pendidikan, 2016)
The procedure of this study refers to the development of procedural models Borg & Gall simplified in accordance with the needs of research. Starting from the Needs Identification, Formulation Objectives, Content Development, Validation, and then do the Revision products according to suggestions and comments matter experts and media experts, the last stage of product trials conducted to 20 students. The analysis showed that the Interactive Multimedia learning media is in the very good category. For material aspects included in the excellent category (4.64). For the aspects of media presentation included in the excellent category (4.58). Furthermore, the test results are limited practicalities of media use are in the very good category (4.4).